2004
DOI: 10.1128/mcb.24.19.8567-8575.2004
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Function but No Gain of Function Caused by Amino Acid Substitutions in the Hexapeptide of Hoxa1 In Vivo

Abstract: Homeodomain containing transcription factors of the Hox family play critical roles in patterning the anteroposterior embryonic body axis, as well as in controlling several steps of organogenesis. Several Hox proteins have been shown to cooperate with members of the Pbx family for the recognition and activation of identified target enhancers. Hox proteins contact Pbx via a conserved hexapeptide motif. Previous biochemical studies provided evidence that critical amino acid substitutions in the hexapeptide sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 41 publications
(62 reference statements)
2
42
0
Order By: Relevance
“…HOXA1 is a key gene in skull development, and it is a retinoic acid (RA) direct target gene (Ijichi and Ijichi, 2002). Mice with mutations in the HOXA1 hexapeptide motif show skeletal defects (Remacle et al, 2004). Similar results were reported by Martinez-Ceballos et al (2005), who showed that the disruption of the HOXA1 gene results in abnormal ossification of the skull.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…HOXA1 is a key gene in skull development, and it is a retinoic acid (RA) direct target gene (Ijichi and Ijichi, 2002). Mice with mutations in the HOXA1 hexapeptide motif show skeletal defects (Remacle et al, 2004). Similar results were reported by Martinez-Ceballos et al (2005), who showed that the disruption of the HOXA1 gene results in abnormal ossification of the skull.…”
Section: Discussionsupporting
confidence: 58%
“…It is well known that HOX proteins participate in many common developmental processes during normal embryogenesis. Several reports have indicated that HOX genes play a regulatory role in skeletogenesis (Goff and Tabin, 1997;Kanzler et al, 1998;van den Akker et al, 2001;Remacle et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Tests of mutant Hox proteins in Drosophila and in mice have demonstrated the importance of the YPWM motif for Hox function in vivo, although both loss-and gain-of-function phenotypes were observed (Chan et al, 1996;; Medina-Martinez and Ramirez-Solis, 2003; Merabet et al, 2003;Remacle et al, 2004;Zhao et al, 1996). In vitro, the YPWM region has been shown to mediate Hox interactions with the PBC family of homeodomain proteins (Chang et al, 1995;Johnson et al, 1995;Knoepfler and Kamps, 1995;Neuteboom et al, 1995;Passner et al, 1999;Phelan et al, 1995;Piper et al, 1999;Shanmugam et al, 1997).…”
Section: Cooperative Repression and The Ubx Ypwm Regionmentioning
confidence: 99%
“…Homozygous HOXA1 mutations, which have occurred in several human populations, are viable but cause either BosleySalih-Alorainy syndrome or Athabascan brainstem dysgenesis syndrome (Bosley et al 2008;Bertrand et al 2011). Surprisingly, homozygous Hoxb1 A1 swapped mice (i.e., mice expressing HoxA1 protein from both Hoxb1 alleles, with no expression of HoxB1) show no detectable phenotypic change relative to wild type under laboratory conditions despite a 15% amino acid sequence difference at the homeodomains and a mere 49% identity overall (Remacle et al 2004;Tvrdik and Capecchi 2006). In hemizygous animals, which express only one Hoxb1 A1 swapped allele over Hoxb1 null, fewer facial motor neurons are generated, resulting in hypomorphism of the seventh cranial nerve.…”
mentioning
confidence: 99%